Phytochemical Constituents, Nutritional Composition, and Pharmacological Potentials of Mangifera foetida: A Comprehensive Review - Alifiyah, Na'ilah Insani; Aryanto, Arie; Zikriyani, Hikmah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Mangifera foetida, commonly referred to as bacang, is a tropical fruit tree of the Anacardiaceae family widely used in traditional medicine throughout Southeast Asia for a variety of therapeutic purposes. Recent scientific studies have validated many of these ethnomedicinal uses by uncovering a diverse phytochemical composition alongside notable pharmacological activities. This review synthesizes current knowledge on the nutritional content, bioactive compounds, and pharmacological effects of M. foetida, with particular focus on its antioxidant, antimicrobial, cytotoxic, antidiabetic, and anti-inflammatory properties. Key secondary metabolites, including mangiferin, phenolic compounds, flavonoids, and essential oils, are believed to underpin its therapeutic efficacy. Moreover, the fruit and other plant parts provide considerable nutritional benefits, supplying essential vitamins, minerals, and dietary fiber. Despite these promising findings, further investigations are needed to clarify underlying mechanisms, improve extraction techniques, and evaluate clinical effectiveness. This review seeks to establish a comprehensive reference to support future research and facilitate the development of M. foetida-derived nutraceuticals and pharmaceuticals.